Knowledge and use of preventive measures against malaria in endemic and non-endemic villages in Northern Thailand - Birgit H.B. Van Benthem (2018)
The objective of this study was to determine the frequency and determinants of knowledge of malaria in four sites in northern Thailand, and to compare the use of prevention measures between people with and without a knowledge of malaria. An epidemiological survey was conducted in January 2002 among 857 persons living in four sites in northern Thailand. Of the 857 persons, 53% had a knowledge of malaria, ranging from 38% and 51% in non-endemic to 76% and 77% in endemic sites. Headache (89%), shivering (83%) and fever (79%) were the most frequently mentioned symptoms. Younger persons had more knowledge of malaria than older persons; adjusted Odds Ratio (aOR): 3.91 [95% confidence interval (Cl): 2.32-6.56] for the 15-29 age group compared to persons 60 years and older. In comparison to men, knowledge of malaria was significantly lower among women (aOR: 2.00, 95%-CI: 1.47-2.70). Persons with knowledge reported a significantly higher use of prevention measures than persons without knowledge of malaria.